Proceedings of the Proceedings of the 1st International Conference on Statistics and Analytics, ICSA 2019, 2-3 August 2019, Bog 2020
DOI: 10.4108/eai.2-8-2019.2290473
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Model of Seasonal ARIMA-ANN to Forecast Tourist Arrivals through Minangkabau International Airport

Abstract: The number of tourist arrivals forecasting is required for the future development of tourism industry to improve the economic growth. The number tourist arrivals data can be analyzed by building a model so that it will help to find out the number of tourist arrivals in the next period which is through Minangkabau International Airport. The linear model that is used is Seasonal Autoregressive Integrated Moving Average (SARIMA) used and continued to build a nonlinear model of the residual SARIMA model using Arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The Aravalli, Ganges, Brahmaputra, and Indus are four significant river systems in India, each with a substantial catchment area and drainage density. All of these river systems have several tributaries that run the length and width of India, making it more vulnerable to flooding [67]. Consequently, during the years 1987 and 1993, the cycle of floods followed by severe drought and its impact on water shortage in Chennai was at its peak.…”
Section: Discussionmentioning
confidence: 99%
“…The Aravalli, Ganges, Brahmaputra, and Indus are four significant river systems in India, each with a substantial catchment area and drainage density. All of these river systems have several tributaries that run the length and width of India, making it more vulnerable to flooding [67]. Consequently, during the years 1987 and 1993, the cycle of floods followed by severe drought and its impact on water shortage in Chennai was at its peak.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained that the accuracy of the SARIMA -SVM hybrid is better than with each method-another study hybrid ARIMA with ANN for forecasting pollution index in cities in Southeast Asia [14]. Furthermore, the study used the same method to predict tourists arriving at Minangkabau international airport [15]. Moreover, for modeling and evaluating the data from a residential district in Berlin [16].…”
mentioning
confidence: 99%
“…Neural network models could be a potential alternative to the traditional linear time series models. Recently, many studies have integrated time series analysis and neural network framework together, a combination of Seasonal Autoregressive Integrated Moving Average (SARIMA) and Nonlinear Autoregressive Neural Network (NARNN) model, in medical sciences [3] [4] [5] [6], business [7], tourism [8]. From these studies reported, this hybrid model can explore the reliable model to forecast the time series for a better performance.…”
mentioning
confidence: 99%